2021
DOI: 10.3390/rs13224548
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Marine Plastic Debris in a Beach Environment Using Spectral Analysis

Abstract: Marine plastic debris (MPD) is a globally relevant environmental challenge, with an estimated 8 million tons of synthetic debris entering the marine environment each year. Plastic has been found in all parts of the marine environment, including the surface layers of the ocean, within the water column, in coastal waters, on the benthic layer and on beaches. While research on detecting MPD using remote sensing is increasing, most of it focuses on detecting floating debris in open waters, rather than detecting MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
4
14
0
Order By: Relevance
“…According to research by Guffogg et al [88], spectral feature analysis enables detection of synthetic material at a sub-pixel. The minimum surface cover required to detect plastic on a sandy surface was found to be merely 2-8% for different polymer types.…”
Section: Challenges In Plastic Detection and Future Opportunities For...mentioning
confidence: 99%
“…According to research by Guffogg et al [88], spectral feature analysis enables detection of synthetic material at a sub-pixel. The minimum surface cover required to detect plastic on a sandy surface was found to be merely 2-8% for different polymer types.…”
Section: Challenges In Plastic Detection and Future Opportunities For...mentioning
confidence: 99%
“…Several studies have been looking for a comprehensive study on this topic. For example, not only Gallo F et al (2018) research shows 8% million tons of plastic debris entering the ocean [8] but also Guffogg J A et al (2020) and Borelle S B et al (2020) showed 0.8-2.7 million of ocean plastics [9,10]. Jambeck et al (2015) estimated that 4.8 to 12.7 million metric tons of plastic from land-based activities entered the world's oceans [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the issue of marine debris, several fundamental studies explore the potential to detect plastic pollution with surveys and observations in laboratories [8,12]. However, assessing marine plastic debris was time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Guffogg et al [20] noted that an obstacle for spectral detection on some beaches was that a large percentage of the plastic debris was shoes, predominantly flip flops, with polyurethane foam not having received as much focus as other plastics. They found that between 2-8%, depending on the plastic polymer, of a unit area must be covered in plastics before the material can be spectrally separated from a non-contaminated area only containing sand.…”
Section: Introductionmentioning
confidence: 99%